Crystallinity and composition engineering of organic crystal derived 1D carbons for advanced Li-metal based batteries - Park, Minsu; Lee, Kwonyun; Kang, Min Sung; Woo, Sujeong; Choi, Wootaek; Kim, Hyein; Kwon, Woong; Choi, Junghyun; Cho, Sung Beom; Jeong, Euigyung; Kim, Patrick Joohyun (Carbon, 2025)
Lithium (Li) has garnered considerable interest in the battery industry owing to its outstanding theoretical capacity (3860 mAh g−1) and low redox potential (−3.04 V vs. standard hydrogen electrode). Unfortunately, the practical applications of Li-metal batteries (LMBs) are impeded by low coulombic efficiency and dendritic Li formation during the charging/discharging process. One of viable strategies for overcoming these challenges involves the use of N-rich carbons in designing functional separators and current collectors. In this study, the potential of organic crystal material (Pigment Red 122; PR122) as a carbonizable nitrogen-rich material was investigated to assess its impacts on the electrochemical performance of Li-ion batteries (LIBs) and LMBs. The carbonization temperature of PR122 was precisely controlled to alter the overall content of nitrogen element in the carbon backbone. Each prepared N-rich carbon was applied to modify the surface of each separator and current collector. The PR122-derived carbon pyrolyzed at a high temperature of 1500 °C (PR|C1500) demonstrated lower discharge capacity. However, it exhibited better electrochemical kinetics than the PR122-derived carbon pyrolyzed at a lower temperature of 600 °C (PR|C600) in LIBs. In the case of LMBs, the Li/Cu cell with a PR|C600 coated separator delivered better cycle stability than the Li/Cu cell with a PR|C1500 coated separator. These results suggest that both the nitrogen content (specifically pyridinic-N and pyrrolic-N) and degree of crystallinity in the carbon platform significantly affect the electrochemical stability and kinetics of LIBs and LMBs. The foregoing is further verified by analysis using the density functional theory-based finite element method.
Keywords: Carbonisation; Current-collector; Derived carbons; Ion batteries; Li metal; Lithiophilicity; Lithium metals; N-rich carbon; Organic crystal; Organic pigments; Carbonization; Li metal; Lithiophilicity; N-rich carbon; Organic pigment